Membangun Entreprenuership dengan Hek Pedi Gelis (Hidupkan Ekstrakurikuler Pengembangan Diri dan Gerakan Literasi Madrasah) di MIN 4 Sragen Jawa Tengah - Rohmawati Rohmawati (Madaris: Jurnal Guru Inovatif, 2024)
This scientific work aims to build students' spirit of entrepreneurship through learning processes and extracurricular activities. Entrepreneurship at Madrasah Ibtidaiyah is an attempt to shape the character of self-confidence, unyielding persistent and innovative. It can be obtained from the integrated learning process and from extracurricular activities that are tailored to the interests, talents and needs of students and madrasah. The subjects of this scientific that are all of madrasah residents, that are totaling 338 students, teachers, employees and heads of MIN 4 Sragen. All madrasah resident are directly involved in the learning process, character building with entrepreunerial spirit and extracurricular activities. The writer as head of the madrasa is involved in managerial madrasah. The results of this scientific work can be seen that the various activities of Hek Pedi Gelis are of a great variety and can be developed according to the needs of students and madrasah. Hek Pedi Gelis does not directly refer to the type of extracurricular activities and learning methods that must be used but can be adjusted to interest, talent, and innovation. Hek Pedi Gelis activities can change according to the situation and conditions of madrasah, students, teachers and the community. With Hek Pedi Gelis, you can build entrepreneurship in MIN 4 Sragen.